2019
DOI: 10.1002/sdtp.12991
|View full text |Cite
|
Sign up to set email alerts
|

43‐3: 14 Inch Flexible LCD Panel with Colorless Polyimide

Abstract: We successfully realized 14 inch flexible LCD display with FHD resolution. The LCD panel has the thickness less than 0.3 mm, which using new type of colorless PI as substrate. The flexibel LCD is IPS mode. The key technology includes the conbination of indium gallium zinc oxide (IGZO) TFT , Color filter on Array substrate(COA)and Black Photo Spacer(BPS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The active matrix (AM) mini‐LEDs full‐color display based on a glass substrate in our previous work was demonstrated that active matrix thin film transistor has a promising application for large‐size display 21 . Based on some researchs of flexible display technloy, utilized the glass substrate coated and cured and cured colorless PI substrate and laser lift off (LLO) process could be a candidate for flexible substrate 20,22‐24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active matrix (AM) mini‐LEDs full‐color display based on a glass substrate in our previous work was demonstrated that active matrix thin film transistor has a promising application for large‐size display 21 . Based on some researchs of flexible display technloy, utilized the glass substrate coated and cured and cured colorless PI substrate and laser lift off (LLO) process could be a candidate for flexible substrate 20,22‐24 …”
Section: Introductionmentioning
confidence: 99%
“…21 Based on some researchs of flexible display technloy, utilized the glass substrate coated and cured and cured colorless PI substrate and laser lift off (LLO) process could be a candidate for flexible substrate. 20,[22][23][24] In this study, an 8-inch flexible full-color mini-LED display was fabricated in combination red, green, and blue (RGB) mini-LED. The display adopted the colorless polyimide (CPI) as substrate, driven by active matrix (AM) indium-gallium-zinc oxide (IGZO) thin-film transistor (TFT).…”
mentioning
confidence: 99%
“…For example, LCDs possess high reliability, whereas OLEDs exhibit a high contrast ratio. Plastic LCDs that take advantage of the characteristics of standard LCDs have also been recently developed 1–5 …”
Section: Introductionmentioning
confidence: 99%
“…Benefit from the great viewing experience, curved LCD are integrated into various products, including TVs, monitors and automotive displays, leading to the remarkably increasing demands of curved LCD panels in the market recently [1]. Although the active-matrix organic light-emitting diode (AMOLED) is also a good candidate for curved displays, in certain application areas that no repeated bending is required and the radius of curvature is adaptable, the curved LCD on thin glass substrates is more competitive due to its relatively low cost and high reproducibility [2][3][4][5][6]. However, the curved LCDs based on thin glass substrates suffer from an issue of uneven brightness among the LCD panels.…”
Section: Introductionmentioning
confidence: 99%